2015
DOI: 10.1140/epje/i2015-15138-8
|View full text |Cite
|
Sign up to set email alerts
|

Snap-off production of monodisperse droplets

Abstract: Abstract. We introduce a novel technique to produce monodisperse droplets through the snap-off mechanism. The methodology is simple, versatile, and requires no specialized or expensive components. The droplets produced have polydispersity < 1% and can be as small as 2.5 µm radius. A convenient feature is that the droplet size is constant over a 100-fold change in flow rate, while at higher flows the droplet size can be continuously adjusted.Microfluidics applications often require emulsions with a wide range o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…1A. The dispersed phase forms a growing spherical droplet that becomes unstable at some critical size and subsequently snaps-off [9]. Figure 1B illustrates schematically the location and relative values of the relevant pressures, which we now describe.…”
Section: Theorymentioning
confidence: 93%
See 4 more Smart Citations
“…1A. The dispersed phase forms a growing spherical droplet that becomes unstable at some critical size and subsequently snaps-off [9]. Figure 1B illustrates schematically the location and relative values of the relevant pressures, which we now describe.…”
Section: Theorymentioning
confidence: 93%
“…The instability requires no viscous interaction, but is due entirely to changes in the curvature of the interface between the two phases, affecting the Laplace pressure. We have previously found that the resulting droplets are highly monodisperse [9], as the system becomes unstable immediately after the protrusion of the dispersed phase reaches a critical size. The snap-off phenomenon has been studied and used to produce droplets in many different geometries [4,5,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations